Disability sport - DePauw, Karen P.; Gavron, Susan J. 1947- (Champaign, IL Human Kinetics, 2005)
Disability Sport, Second Edition, provides a comprehensive and practical look at the past, present, and future of disability sport. Topics covered are inclusive of youth through adult participation with in-depth coverage of the essential issues involving athletes with disabilities. This new edition has updated references and new chapter-opening outlines that assist with individual study and class discussions. The book contains an up-to-date and comprehensive synthesis of information on disability sport in its historical context; organizations, competitions, and sport opportunities for athletes with disabilities; international perspectives; and coaching and training of athletes with disabilities, including sports medicine issues, activity modifications, equipment uses, and event management for both adults and children. In addition, the book addresses current challenges and controversies in disability sport (e.g., inclusion and integration, classification, ethics issues, doping, and equity issues) and looks into the future of disability sport. It includes minibiographies of standouts in disability sport from around the world. Students and professionals can use Disability Sport, Second Edition, as a springboard to further research; as an up-to-date reference; and as a tool in working with, or preparing to work with, athletes with disabilities.
Part I. Overview of Sport and Individuals with Disabilities -- Chapter 1. Introduction ; Sport in Society ; Athletes With Disabilities ; Defining Terminology ; In the Context of Sport ; Concluding Comments -- Chapter 2. Historical Context of Disability and Sport ; Historical Treatment of Persons With Disabilities ; Historical Perspectives of Physical Activity and Sport ; Concluding Comments -- Chapter 3. History of Disability Sport ; International Disability Sport ; United States Disability Sport ; Historical Perspectives on Research ; Trends and Milestones in Disability Sport ; Concluding Comments -- Chapter 4. Structure and Organizations for Disability Sport ; International Structure for Disability Sport ; International Disability Sport Organizations ; United States Structure of Disability Sport ; United States Disability Sport Organizations ; Concluding Comments -- Chapter 5. Competitions and Sport Opportunities for Athletes With Disabilities ; Paralympic Games ; Deaflympics ; Special Olympics International ; Additional International Games for Athletes With Disabilities ; National Disability Sport Opportunities ; Intercollegiate and Interscholastic Athletic Programs ; Concluding Comments -- Chapter 6. Sport and Disability: A World View ; Terminology ; International Perspectives: Late 20th Century ; European Charter for Sport for All ; European Perspectives ; Canadian Perspectives ; Perspectives From Oceania ; Perspectives From Asia ; Perspectives From the African Continent ; Perspectives From the Middle East ; Concluding Comments -- Part II. Sport and Sport Performance -- Chapter 7.Sports for Athletes With Disabilities ; Major Competitions for Disability Sport: The Paralympic Games, Special Olympics, and the Deaflympics ; Creating Equal Playing Fields Within Disability Sport ; The Sporting Events ; Concluding Comments -- Chapter 8. Coaching and Training Athletes With Disabilities ; Research and Coaching ; The Research Foundation for Disability Sport ; Summary of Selected Research Findings ; General Principles of Coaching Athletes With Disabilities ; Selected Disabilities and Specific Strategies ; Concluding Comments -- Chapter 9. Sports Medicine and Athletic Training for Athletes With Disabilities ; Sports Medicine ; Sports Medicine and Disability Sport ; Injuries, Incidence, Care, Prevention ; Treatment Considerations ; Training ; Exercise Considerations ; Concluding Comments -- Chapter 10. Sport Equipment ; Equipment Enhances Function ; Personal Equipment ; Activity-Specific Equipment ; Environmental Technologies ; Making Sport Technology "Fit" ; Resources for Finding the Right Equipment ; Making Equipment Adaptations ; Concluding Comments -- Chapter 11. Event Management ; Managing the Sport Event ; Initial Planning ; Structure and Organization ; Committees and Functions ; Event Management Focal Points for Individuals With Disabilities ; Media and Athletes With Disabilities ; Planning for International Sport Events ; Concluding Comments -- Part III. The Changing Landscape of Disability Sport -- Chapter 12. Challenges and Controversies in Disability Sport ; Inclusion and Integration ; Classification ; Ethics Issues ; Doping in Disability Sport ; Media Representation ; Youth Sport Development ; Marketing Disability Sport ; Concluding Comments -- Chapter 13. Female Athletes With Disabilities in Sport ; Historical Perspectives ; Female Athletes in the Olympic Games ; Female Athletes in Marathons ; Equity Issues ; Concluding Comments -- Chapter 14. The Future of Disability Sport ; Trends ; Inclusion ; Images of Disability Sport ; Sport, Society, and Disability ; Concluding Comments -- Appendix A. Chronology and Significant Milestones of Disability Sport -- Appendix B. List of Abbreviations -- Appendix C. Outdoor Recreation Activities for Individuals With Disabilities -- Appendix D. Selected International Disability Sport Organizations -- Appendix E. Selected U.S. and Canadian Disability Sport Organizations -- Appendix F. Paralympic Committees by Region -- Appendix G. Periodical and Journal Resources -- Bibliography -- Index -- About the authors.
Revised edition of Disability and sport, 1995
Includes bibliographical references
Keywords: Sports for people with disabilities